THE INFLUENCE OF DIGITALIZATION ON THE DEVELOPMENT OF INNOVATIVE BUSINESS MODELS IN THE LOGISTICS SPHERE - KHARUN, Olena; HRYTSYNA, Lesia (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article explores various approaches to understanding the category "digitalization" in domestic and foreign literature, which is interpreted as the process of using, applying, transferring and converting information into a digital format; system of data collection, storage, analysis, application of artificial intelligence; transformation of penetration of digital technologies, regarding the optimization of business processes and business models. It is proposed to consider digitalization as a process of transformation of activity, which involves the use of digital innovative technologies to optimize business models, increase income from conducting business activities and improve the communication system with consumers. The constituent elements of digitization, its advantages and disadvantages are defined and systematized. Four main levers of digitalization, through which the digital transformation of the business model of the enterprise works, and three ways of impact of digitalization on the change of companies and their business models are highlighted. It is indicated that the system of digitalization in the field of logistics can be represented in the form of a community formed on the basis of the use of digital platforms and their applications, by developers, providers and users of logistics services, agents with experience in the field of logistics and possessing competencies acquired through the use of digital information technologies. The list of the most common innovative digital technologies in the management system of logistics business models is presented and the areas of their application are defined. The need to use tools for digital transformation of the business model of supply chains using the identified global trends in the development of logistics and supply chains for the future and adjusting them to solve more pressing global problems is substantiated.
Keywords: digitization; digitalization; business model; supply chains; logistics sphere; innovative digital technologies